Renewable energy in power systems - Freris, Leon, ....-; Infield, David, ....- (Chichester : Wiley, 2008)
Renewable Energy (RE) sources differ from conventional sources in that, generally they cannot be scheduled, they are much smaller than conventional power stations and are often connected to the electricity distribution system rather than the transmission system. The integration of such time variable 'distributed' or 'embedded' sources into electricity networks requires special consideration.
Keywords: Duurzame energie